1981
DOI: 10.1901/jaba.1981.14-223
|View full text |Cite
|
Sign up to set email alerts
|

Training Parents in Behavioral Self‐management: An Analysis of Generalization and Maintenance

Abstract: on levels of disruptive child behavior and the accuracy with which parents implemented programs. Data were collected from five families in three main settings: the initial training setting (the home), a variety of generalization settings in the community, and the family breakfast. A multiple baseline across subjects design was used. Instructions plus Feedback comprised instructing parents to use a range of behavior management procedures and provided home-based differential feedback concerning accuracy of progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
94
0
4

Year Published

1985
1985
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 131 publications
(103 citation statements)
references
References 14 publications
5
94
0
4
Order By: Relevance
“…The program began on a small scale as a home-based, individually administered training program for parents of disruptive preschool children (Sanders & Glynn, 1981). It has evolved over the past 25 years into a comprehensive public health model of intervention.…”
mentioning
confidence: 99%
“…The program began on a small scale as a home-based, individually administered training program for parents of disruptive preschool children (Sanders & Glynn, 1981). It has evolved over the past 25 years into a comprehensive public health model of intervention.…”
mentioning
confidence: 99%
“…The addition of planned activities may have failed to produce significant group differences because of ceiling effects. Setting specific training procedures such as planned activities may be more useful when parents fail to spontaneously generalize their skills across home settings or when generalization to the community is required (Sanders & Glynn, 1981;Sanders, 1982). In previous research, planned activities training has tended to be used with parents who have failed to spontaneously generalize their skills to all relevant settings (Sanders, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…This lack of consistent response by parents to training procedures has prompted researchers to identify marital, psychopathological, attitudinal, socioeconomic, and community contact variables that will discriminate families who are successful and unsuccessful in parent training (Griest & Wells, 1983;Wahler & Graves, 1983). Other research has shown that parents may have more difficulty in applying contingency management procedures in some settings than in others (Miller & Sloane, 1976;Sanders & Glynn, 1981). For example, some parents may require setting specific interventions to manage their children at mealtimes, bedtime, or on visits to the community such as shopping trips or dining out (Bauman, Reiss, Rogers, & Bailey, 1983;Sanders & Hunter, 1984).…”
mentioning
confidence: 99%
“…Treatment outcome studies often report large effect sizes (Serketich & Dumas, 1996), with good maintenance of treatment gains (Forehand & Long, 1988). Treatment effects have been shown to generalize to school settings (McNeil, Eyberg, Eisenstadt, Newcomb, & Funderbunk, 1991) and to various community settings (Sanders & Glynn, 1981). Parents participating in these programs are generally satisfied consumers (Webster-Stratton, 1989).…”
Section: The Strengths and Limitations Of Parenting Interventionmentioning
confidence: 99%